Divergence in social foraging among morphs of the three‐spined stickleback, Gasterosteus aculeatus. (25th July 2014) - Ólafsdóttir, Guðbjörg Ásta; Andreou, Alexandreou; Magellan, Kit; Kristjánsson, Bjarni K.
<x xml:space="preserve">Abstract</x> Foraging in social groups has a number of benefits but can also increase the risk of exploitation. High tendency to shoal may be correlated with groups foraging, although facultatively social fish adjust both shoaling decisions and food resource defence based on intrinsic and extrinsic factors. The main aim of this study was to examine the relationships between shoaling, solitary foraging and aggression, forager tolerance of conspecifics joining at a discovered food patch and forager exploitation of resources discovered by others. We used two intra‐lacustrine three‐spined stickleback morph pairs, lava and mud, and monomorphic morphs from each of lava and mud habitats. The lava morph formed less cohesive shoals, was bolder during solitary foraging, approached and entered an occupied food patch less frequently than the mud morph, suggesting a link between shoaling and the propensity for social foraging. However, shoaling tendency and joiner tolerance were not correlated at a population level. Intralacustrine lava and mud morphs differed more markedly in joiner tolerance than morphs from single habitat lakes, whereas the opposite was true for shoaling tendency. We conclude that, in addition to differentiation in shoaling tendency, the lava and mud morphs differ in social foraging and these variations may act to promote population divergence. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 194–203.